THE LEGAL ACT ON COUNTERFEITING THE COVID-19 VACCINE IN INDONESIAN HEALTH LAW - Lasmadi, Sahuri (International Journal of Law Reconstruction, 2021)
The International Criminal Police Organization has officially issued a global warning to law enforcement officials in 194 member countries to prepare to prevent and deal with various world criminal networks that will seek to utilize the Covid-19 vaccine, both physically. The online form is counterfeiting the Covid-19 vaccine. This study aims to analyze the criminal act of counterfeiting the Covid-19 vaccine from the Health Law in Indonesia. The research method used is the Normative Law research method, which examines library materials or secondary data. Normative legal research is also called doctrinal legal research.Â  The criminal act of counterfeiting the Covid-19 vaccine is generally regulated in Article 386 Paragraph 1 of the Criminal Code relating to acts of fraud and forgery. However, it is specifically regulated in the provisions regarding penalties for distributing fake vaccines in Indonesia as regulated in Articles 196, 197, 198, and 201 Act No. 36 of 2009 concerning health. The ingredients are everyone deliberately and producing and circulating counterfeit vaccine preparations. For the criminal act ofCovid-19 vaccine counterfeiting corporate, the corporation can be subject to additional penalties in the form of revocation of business licenses and revocation of legal entity status.